MANAGEMEN MUTU TERPADU BERBASIS KINERJA - Nur Setyaningrum (Mozaic : Islam Nusantara, 2022)
Performance-based management is more directed to work processes, management, development and related rewards. Where the ability, motivation, and opportunities interact with each other. Islamic educational institutions, especially Quran Education Parks are growing from year to year, but in the process of their managing, they are still limited to "volunteering", so that performance is not often proportional to the rewards and awards given. Finally, this "volunteering" parameter cannot produce a balanced performance between educators. This also has the potential to affect the competence of educators and have an effect on students. Alif Iqra as a non-formal institution engaged in Islamic education, especially Quran education, seeks to improve the performance base. One of the stimuli is the form of the Alif Award and periodic evaluations. This research is a qualitative research with an exploratory approach from an educational institution about a certain phenomenon, namely the Alif Award program. The results showed the Alif Award is seen as a form of fair competition that includes a cumulative assessment of performance for one year. This is one of the external motivations for teachers to improve their performance accompanied by regular evaluations and competency improvement. Among the evaluations and periodic programs that give meaning to educators are the monthly meeting program and the “call cloud”. This program is proven to make educators have independent awareness to control and evaluate their performance